Species structure and year-to-year dynamics of nekton biomass in the upper epipelagic layer of the Pacific waters at Kuril Islands in summer periods of the 2000s - Alexey A. Khoruzhiy; Svetlana V. Naydenko (Известия ТИНРО, 2014)
The North-West Pacific waters at Kuril Islands are characterized by high productivity because of high water dynamics due to interaction of the Kamchatka, Oyashio, and Kuroshio Currents and tidal mixing. Abundance, species composition, and spatial density of nekton in the upper epipelagic layer (0-50 m) of this area are considered on the data of trawl surveys conducted in June-July of 2004-2012. In total, 97 species of nekton are found in the trawl catches, including 73 species of fish and 24 species of cephalopods belonged to 15 genera and 8 families. Myctophidae have the highest species richness and biomass among fish (12 species, 33% of the total nekton biomass), and Gonatidae have the highest number of species and biomass among cephalopods (13 species, 11 %). Mesopelagic fishes, being temporary inhabitants of the epipelagic layer, dominate in the nekton community (54 species, 60 % of total biomass), they migrate to the upper layer at night for feeding. Other important ecological groups are salmons migrating to spawning grounds and subtropical species migrating to feeding grounds. Ratio between these groups is very variable. Total abundance of nekton varied from 1.1 t/km² in 2010 to 4.6 t/km² in 2004, on average 2.4 t/km². Range of its spatial variation is even higher: 1.1-6.0 t/km²; it depends on evenness of species composition and abundance of dominant species; generally both total abundance and species richness increase from the north to the south, as boreal species are replaced by low-boreal and subtropical ones. From the other hand, the abundance and species richness increase from the shore toward the ocean: the total number of nekton species increases from 42 to 76, and the number of dominant species - from 4 to 10, so structure of the nekton community becomes more evened and polydominant. The highest abundance and species richness are observed in the Subarctic Front zone. Mean total biomass of nekton in the epipelagic layer of the surveyed area is estimated as 2442 · 103 t including 1.6-2.5 million t (37-60 %) of mesopelagic fish that was the major group of nekton in all years except 2012, when the biomass of mesopelagic fish was only 378 · 103 t (21 %) while the portion of salmons increased to 40 % because of extremely high biomass of pink salmon (27 % of the total nekton biomass). Year-to-year changes of the nekton abundance in the surveyed area are characterized by negative trend, with its minimal values in 2008, 2010, and 2012, but it is considered as a temporary tendency.